Using the text-messaging program SmokefreeTXT to support smoking cessation for nondaily smokers. (3rd July 2019) - Hoeppner, Bettina B.; Hoeppner, Susanne S.; Schick, Melissa R.; Milligan, Connor M.; Helmuth, Eric; Bergman, Brandon G.; Abroms, Lorien C.; Kelly, John F.
Abstract: Introduction: Smoking cessation interventions for nondaily smokers are needed. The current study explores the fit of the text-messaging intervention SmokefreeTXT for nondaily smokers. Methods: Adult nondaily smokers ( N  = 32; mean age = 35 ± 12, 64% female, 53% non-Hispanic White) were enrolled in SmokefreeTXT. SmokefreeTXT usage data were recorded passively, theorized mechanisms of change were assessed at baseline and 2, 6, and 12 weeks after the chosen quit day, and EMA protocols captured real-time cigarette reports at baseline, and during the first two weeks after the quit day. Results: Most participants completed the SmokefreeTXT program and responded to system-initiated inquiries, but just-in-time interaction with the program was limited. In retrospective recall at treatment end, content of the text-messages was rated as "neutral" to "helpful." Within-person change was observed in theorized mechanisms, with less craving ( p  < 0.01), increased abstinence self-efficacy (external: p  < 0.01; internal: p  < 0.01), and poorer perceptions of pros of smoking (psychoactive benefits: p  < 0.01, pleasure p  < 0.01; and pros: p  < 0.01) reported after SmokefreeTXT initiation compared to baseline. Exploratory analyses of real-time reports of smoking (225 cigarette reports in N  = 17 who relapsed) indicated that cigarettes smoked in the first two weeks after quitting were more likely to occur to reduce craving (OR = 2.21[1.21–3.72]), and less likely to occur to socialize (OR = 0.06[0.01–0.24]), between 19:00 and 23:00 (OR = 0.34[0.17–0.66]), and on Saturdays (OR = 0.59[0.35–0.99]) than prior to quitting. Conclusions: While well accepted by nondaily smokers, SmokefreeTXT could potentially be improved by targeting cons of smoking, enhancing engagement with the just-in-time component of SmokefreeTXT, and tweaking the timing of text-messages.